Effect of prenatal EPA and DHA on maternal and cord blood insulin sensitivity: a secondary analysis of the mothers, omega 3, and mental health study - Joey A. England; Joses Jain; Bradley D. Holbrook; Ronald Schrader; Clifford Qualls; Ellen Mozurkewich (BMC, 2019)
Abstract Background We sought to determine whether prenatal supplementation with the omega-3 fatty acids eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) would increase markers of insulin sensitivity in maternal or cord blood compared with placebo supplementation. A secondary aim was to evaluate the association of serum EPA and DHA fractions with adiponectin, leptin and the adiponectin:leptin ratio (ALR). We hypothesized that omega-3 fatty acid supplementation would increase markers of insulin sensitivity in maternal and umbilical cord plasma. Methods We analyzed stored plasma samples collected from a prior 3-arm prospective, double-blinded, randomized controlled trial in which 126 women with singleton pregnancies between 12- and 20-weeks' gestation were randomized to receive: 1) an EPA-rich fish oil supplement, 2) a DHA-rich fish oil supplement, or 3) a soy oil placebo. Maternal venous blood samples were collected at 12-20 weeks gestation (before supplementation) and at 34-36 weeks gestation. At delivery, cord blood was collected. Samples were analyzed using sandwich enzyme-linked immunosorbent assay kits to quantify leptin and adiponectin levels which were utilized to calculate the ALR, a proxy measure for insulin sensitivity. Results We found no difference in adiponectin, leptin, and the ALR between the treatment and placebo groups at baseline, after supplementation, or in umbilical cord blood. In regression analyses, higher maternal serum DHA fraction was associated with increased ALR before (p = 0.01) and after (p = 0.04) DHA supplementation. There was no association of EPA fraction with any measure of insulin sensitivity. Cord blood DHA fraction was significantly associated with cord plasma leptin (p = 0.02). Early pregnancy BMI was significantly associated with maternal leptin levels at baseline and in late pregnancy (p < 0.001) and was inversely associated with the ALR (p < 0.001). The ALR decreased significantly between the early and late pregnancy visits (p < 0.001). Pregnancy weight gain was inversely associated with the ALR (P. < 0.02). Conclusions EPA- and DHA- rich fish oil supplementation had no effect on plasma markers of insulin sensitivity. However, maternal serum DHA fraction was significantly associated with markers of insulin sensitivity. Trial registration https://clinicaltrials.gov/, registration number NCT00711971, 7/7/2008.